RESPON CYLINDROCLADIUM SP. TERHADAP FUNGISIDA BERBAHAN AKTIF MANCOZEB SECARA IN VITRO - Pebrian Indra Risky Dalimunthe; Edy Batara Mulya Siregar; Nelly Anna (Program studi Kehutanan USU, 2015)
Cylindrocladium sp. is one of the pathogens trigger dangerous diseases that blight the eucalyptus plant. Fungi is one of the pathogens that attack the breeding ground and nursery eucalyptus in various parts of the world, including Indonesia. Efforts to control its spread by means of direct control is by the use of fungicides. Fungicides are used in this research is a contact fungicide mancozeb 80% active ingredient. The study aims to measure the growth of the colonies, the relative constraints, the density of spores and hyphae shape changes Cylindrocladium sp. after treated with 0, 0.4, 0.8, 1.2 and 1.6 mg / ml. The sample used was taken from the collection of fungi in Forestry Biotechnology Laboratory. The research was conducted in February 2015 until April 2015 at the Biotechnology Laboratory of Forestry, Department of Forestry and in the Laboratory of Disease Study Program Plant Pests and Diseases, Faculty of Agriculture, University of North Sumatra. Results of the study are significant response at each concentration fungicide mancozeb. Response significant effect starting from the 12th day until the 16th day of observation. The response of the real effect is diameter growth, barriers relative density of spores. Besides treatment causes swelling and breakdown of the structure of hyphae. Key Words: Response, In Vitro, Cylindrocladium sp., Fungicide Mancozeb 80% WP